Lipid-lowering effect of combined therapy with high-intensity statins and CETP inhibitors: a Systematic Review and meta-analysis - Xiang, Liubo; Wu, Huan; Zhao, Zhihao; Wu, Tingchun; Lv, Dawei; Wu, Ping; Zheng, Yuhua; Huang, Qianqian; Xu, Tao (Frontiers in Endocrinology, 2025)
BackgroundThis study aimed to evaluate the impact of combining high-intensity statins with CETP inhibitors on lipid levels, as well as to explore their potential clinical significance.MethodsWe conducted a comprehensive search of relevant studies in the PubMed, Embase, Cochrane Library, and Web of Science databases. The Cochrane Risk of Bias Tool RoB 2.0 was employed to evaluate the quality of the included studies. Statistical analyses were carried out using STATA 15 software, with primary outcomes being high-density lipoprotein cholesterol (HDL-C) and low-density lipoprotein cholesterol (LDL-C).ResultsOut of 2,552 records, 7 studies were included in the final analysis. The findings revealed that the combination of high-intensity statins with CETP inhibitors significantly raised HDL-C levels (SMD 2.47 [1.77, 3.18], p < 0.001) and lowered LDL-C levels (SMD -1.75 [-2.19, -1.31], p < 0.001).ConclusionCompared to statin monotherapy, the combination of high-intensity statins and CETP inhibitors resulted in a more pronounced increase in HDL-C and ApoAI, while reducing LDL-C, triglycerides (TG), and ApoB levels, without increasing the incidence of adverse events.